Investigation of Phosphor Chemistry Behavior During Aluminum Production from Alunite - Geidarov, Arif A.; Babayeva, Pervane H.; Turan, M. Deniz; Nizamoglu, Hasan (Springernature, 2025)
This study investigated the processing of alunite ore and the efficient removal of phosphorus (as P2O5) to enhance the quality of the final product. Initially, 0.5 kg of raw alunite was crushed and dehydrated, followed by a series of thermal treatments, yielding 0.412 kg of alunite with a higher impurity content. Subsequently, the processed material was dissolved in a caustic solution, and the phosphorous distribution across various process products was analyzed. The findings revealed that 58.49% of the phosphorus was transferred into the solution phase, while the remainder was retained in the solid residue. A cyclic recycling process was employed to enrich the concentrations of aluminum, vanadium, gallium, and phosphorus in the solution. Subsequently, carbon dioxide was used to neutralize the solution, leading to the precipitation of aluminum hydroxide, with notable phosphorous removal observed at lower pH values. Phosphate ions were effectively precipitated by introducing gypsum, reducing the phosphorus concentration from 4.8 g/L to 2 mg/L, thereby minimizing its detrimental effect on product quality. Characterization studies were conducted using X-ray Diffraction (XRD), Scanning Electron Microscopy with Energy-Dispersive X-ray Spectroscopy (SEM-EDS), and Fourier Transform Infrared Spectroscopy (FT-IR). Overall, this study provides valuable insights into phosphorus control strategies during alunite ore processing and proposes an effective method for lowering P2O5 concentrations in industrial applications.
Keywords: Alunite; Aluminate solution; Suspension; Phosphate ion; Purification of mixtures; Precipitation of phosphorus